Dynamics of the superfluid to Mott-insulator transition in one dimension - Clark, S; Jaksch, D (American Physical Society, 2004)
We numerically study the superfluid to Mott insulator transition for bosonic atoms in a one-dimensional lattice by exploiting a recently developed simulation method for strongly correlated systems. We demonstrate this method’s accuracy and applicability to Bose-Hubbard model calculations by comparison with exact results for small systems. By utilizing the efficient scaling of this algorithm we then concentrate on systems of comparable size to those studied in experiments and in the presence of a magnetic trap. We investigate spatial correlations and fluctuations of the ground state as well as the nature and speed at which the superfluid component is built up when dynamically melting a Mott insulating state by ramping down the lattice potential. This is performed for slow ramping, where we find that the superfluid builds up on a time scale consistent with single-atom hopping and for rapid ramping where the buildup is much faster than can be explained by this simple mechanism. Our calculations are in remarkable agreement with the experimental results obtained by Greiner et al. [Nature (London) 415, 39 (2002)].